Effect of Temperature on Reliability and Degradation of 0.63?m Laser Diode (Baghdad Science Journal, 2012)
The reliability of optical sources is strongly dependent on the degradation and device characteristics are critically dependent on temperature. The degradation behaviours and reliability test results for the laser diode device (Sony-DL3148-025) will be presented .These devices are usually highly reliable. The degradation behaviour was exhibited in several aging tests, and device lifetimes were then estimated. The temperature dependence of 0.63?m lasers was studied. An aging test with constant light power operation of 5mW was carried out at 10, 25, 50 and 70°C for 100hours. Lifetimes of the optical sources have greatly improved, and these optical sources can be applied to various types of transmission systems. Within this degradation range, the device life for system application is estimated to be more than 100 h at 70 ºC at a constant power of 5mW.